Analysis Of The Influence Of Recruitment, Selection And Training On Employees Performance Of PT. Scentium Flavour In Indonesia - Silawati Wijayaguna; Diana Silaswara (Fakultas Bisnis, 2022)
The purposed of this paper was to analyze the effect of recruitment to the employee performance, selection to the employee performance, training to the employee performance and all together to the employee performance. The research was performed by distributing questionnaires, and the research method used a saturated sample which are respondents were used to as a sample. Recruitment (X1), Selection (X2) and Training (X3) variables are simultaneously having a strong connection and positive effect with the employee performance. The results of the partial significance test for the recruitment variable (X1) where the t-test was obtained that the t-value value for recruitment was 5,693 > t-table 1,681 and ,000 <0,05 for the selection variable (X2) where the t-value test was obtained that the t-value selection value 9,115 > t table 1,681 and ,000 < 0,05 while the training variable (X3) where the t value test is obtained that t arithmetic training is 6,382 < t table 1,681 and ,000 < 0,05. The adjusted R2 value shows the coefficient of determination which means the percentage of the contribution of the independent variable Recruitment (X1), Selection (X2) and Training (X3) contributed 66.6% to the employee performance of PT. Scentium Flavours while the 33.4% is influenced by other variables.